Diagnosis and Management of Barret's Esophagus - Adi Wijaya; Dharmika D; Ari F Syam; Toar JM Lalisang (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Incidence of esophageal adenocarcinoma is increasing in western countries and has poor prognosis due to late diagnosis. Barrett’s esophagus is considered as premalignant lesion in which some of squamous epithelium in distal esophagus has been replaced by metaplastic columnar ephithelium. It occurs as complication of longstanding gastroesophageal reflux. Endoscopic examination is very important for early detection especially in patients with chronic symptoms of gastroesophageal reflux disease (GERD) for more than 5 years. Aggressive antireflux treatment may reduce the risk of esophageal carcinoma. However, no single therapeutic modality had been proven superior compare to others, but until now surgery remains the most popular treatment of choice in the management of Barrett’s esophagus.   Keywords: Barrett’s esophagus,GERD, premalignant lesion, management